DAMPAK MUNCULNYA SIMBOL MODERNITAS DI KECAMATAN DENPASAR SELATAN TAHUN 1980 -2014 - Fachzuri R. A., Agus (Humanis, 2017)
South Denpasar District is one of the districts located in the city of Denpasar. In 1980, the government built By Pass Ngurah Rai Road. The presence of this road results in the symbol of modernity such as hotels, restaurants and bars. Such changes become a pull factor for people both inside and outside Bali to come, work and live in South Denpasar District. Those symbols of modernity also have an impact on social change in society, for instance a change in the culture system, changes in the economic system and the loss of the solidarity bond in society of South Denpasar District. In addition, the development of the symbols of modernity in South Denpasar District also have an negative impact on the environment such as the loss of green area around South Denpasar District as well as the emergence of the slums settlements in several villages in South Denpasar District.
Keywords: symbol of modernity, Social Change and Slums